2021
DOI: 10.1097/psy.0000000000001006
|View full text |Cite
|
Sign up to set email alerts
|

Psychobiological Mechanisms in Somatic Symptom Disorder and Depressive Disorders: An Ecological Momentary Assessment Approach

Abstract: Objective: Persistent somatic symptoms cause strong impairment in persons with somatic symptom disorder (SSD) and depressive disorders (DDs). Specific negative psychological factors (NPFs), such as catastrophizing, negative affectivity, and behavioral avoidance, are assumed to contribute to this impairment and may maintain symptoms via dysregulations of biological stress systems. We examined the associations between NPF and somatic symptoms in the daily life of women with SSD or DD and investigated the mediati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 95 publications
1
5
0
Order By: Relevance
“…Acute perceived stress and heightened physiological arousal are, in turn, assumed to aggravate the perception of somatic symptoms 12 . Moreover, we found that lower cortisol levels were prospectivly associated with higher intensity of somatic symptoms in SSD in the same sample as used in the present study 13 . Consequently, HPA axis/ANS dysfunctions can qualify as potential treatment targets in individuals with SSD and DEP 14 .…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…Acute perceived stress and heightened physiological arousal are, in turn, assumed to aggravate the perception of somatic symptoms 12 . Moreover, we found that lower cortisol levels were prospectivly associated with higher intensity of somatic symptoms in SSD in the same sample as used in the present study 13 . Consequently, HPA axis/ANS dysfunctions can qualify as potential treatment targets in individuals with SSD and DEP 14 .…”
Section: Introductionsupporting
confidence: 69%
“…In addition, music might facilitate behavioral activation (e.g., physical activity), which has been shown to be an evidence-based intervention for the treatment of DEP 50 . In individuals with SSD, ruminative thoughts typically focus more strongly on distress-causing bodily perceptions (e.g., pain catastrophizing) and they might try to avoid activating physical activities 13 , 17 . Thus, ‘distraction’ and ‘activation’ via music listening might not be as helpful for reducing subjective stress levels in individuals with SSD compared to individuals with DEP when music is self-administered in daily life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, somatic symptom disorder appears to be associated with altered autonomic functioning at rest and during emotional processing, such that these individuals exhibit lower parasympathetic activity when contrasted with healthy controls ( 15 ). In addition, lower levels of hair cortisol have been reported ( 14 ) and lower levels of salivary cortisol in everyday life have been associated with more intense bodily symptoms in somatic symptom disorder ( 16 ). However, to date, it remains unknown whether individuals with somatic symptom disorder more frequently experience daily life stress and diurnal changes in autonomic and hypothalamic-pituitary-adrenal axis activity, and whether this is affected by the presence of childhood trauma.…”
Section: Introductionmentioning
confidence: 99%
“…Doerr et al, 2015;Mewes et al, 2021). Fourty-two individuals were excluded following this criterion.…”
mentioning
confidence: 99%